A novel composite of nanomagnetite-immobilized-baker's yeast on the surface of activated carbon for magnetic solid phase extraction of Hg(II). (1st January 2015) - Mahmoud, Mohamed E.; Ahmed, Somia B.; Osman, Maher M.; Abdel-Fattah, Tarek M.
Graphical abstract: Schematic diagram of various sorbents. Highlights: A novel nanomagnetic solid phase extraction composite. Adsorptive removal of Hg(II) from water. Optimization of controlling factors. Adsorption isotherm models. Abstract: The lowest concentration level of mercury in human body is dangerous for the health due to its bioaccumulation and high toxicity. Removal of mercury (II) from various samples was explored, studied, optimized and evaluated in the present study by using the combined sorption characteristics of a novel composite based on three sorbent–biosorbent systems. This was accomplished by surface modification of activated carbon with nano-Fe3 O4 and loaded with baker's yeast. The sorbent–biosorbent materials were characterized by using SEM imaging and FT-IR analysis. The magnetic solid phase extraction (MSPE) of Hg(II) from aqueous solutions was studied by measuring the metal sorption capacity and the maximum values were identified in the range of 250–800 μmol g −1 . The factors affecting MSPE process of mercury (II) from aqueous solutions were also optimized including the pH, shaking time, interfering ions, sorbent dosage and initial concentration of Hg(II). The potential applications in removal of Hg(II) from different real matrices including water samples and saving lamb waste materials were also explored. The results of this study refer to the excellent percentage extraction values of mercury (II) (92.0–100.0 ± 1.0–3.0%).